Fatores determinantes da adoção da certificação SISBOV/TRACES na pecuária de corte do estado de São Paulo - Vinholis, Marcela de Mello Brandão (2013)
The increase number of food contamination cases, associated with increasing market competition, fostered the adoption and diffusion of new legal rules and certification systems related to food safety. Technical and sanitary barriers were created by import countries. The European Union has demanded traceability as a condition to have access to its market. These demand had impact on the national regulatory environment for food safety. In 2002, The Brazilian System of Identification and Certification of Bovine and Bubaline Origin (SISBOV) was created. The SISBOV certification is necessary, but not sufficient condition to export to EU market. The farm must also be part of TRACES (Trade Control and Expert System) certification. TRACES is a network created by EU for veterinary health which notifies, certifies and monitors trade in animals and animal products. However, the level of diffusion of this certification is low. A small number of farms have adopted and technological heterogeneity persists in bovine livestock production in Brazil. The aim of this thesis is to identify and analyze determinants of adoption of SISBOV and TRACES certification at the farm level in the State of São Paulo, Brazil. The literature on technology adoption and entrepreneurship provides a theoretical framework to understand how farmers behave with regard to an innovation. A survey questionnaire was used to get the information on farmer and farm characteristics. The logit model was used to analyze the cross section data from a sample of 32 certified farms and 52 non-certified counterfactual farms. The results suggest that the adoption of feedlot production system, associated to the adoption of hedge mechanisms, is an important determinant of the adoption of the certification. There is complementarity between the technologies. Also, the livestock and farm size, education, participation on farmer organization and being a member of a group of farmers informally organized, previous experience with other certification, business travels abroad and access to specialized information by web play a significant role in the adoption of both SISBOV and TRACES certification.